(untitled) (Razão e Fé, 2023)
This brief essay aims to expose some reflections on the social question, seen in the debate about poverty and its consequences for Latin American theology. It also seeks to problematize in the light of the official documents of the Church what is understood and intended by "salvation" from Latin American theologians who make contributions to the theme of the poor and of salvation, poverty and liberation in their socio-political and religious commitments. It is worth, within this horizon, to delineate what relations exist between misery and poverty and their implications in the Latin American theological debate. We understand that the two concepts (poverty and misery) carry different connotations from a sociological and theological point of view, but they can be dialectically reflected upon.